2023
DOI: 10.1002/advs.202306923
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Relay for Nickel‐Catalyzed Decarbonylative Alkylation of Aroyl Chlorides

Tian‐Zhang Wang,
Yu‐Qiu Guan,
Tian‐Yu Zhang
et al.

Abstract: Transition metal‐catalyzed direct decarboxylative transformations of aromatic carboxylic acids usually require high temperatures, which limit the substrate's scope, especially for late‐stage applications. The development of the selective decarbonylative of carboxylic acid derivatives, especially the most fundamental aroyl chlorides, with stable and cheap electrophiles under mild conditions is highly desirable and meaningful, but remains challenging. Herein, a strategy of nickel‐catalyzed decarbonylative alkyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 147 publications
0
3
1
Order By: Relevance
“…Considering certain stability and moderate reactivity of aroyl fluorides among aryl carboxylic acid derivatives, 1 c , d we first selected 4-methoxybenzoyl fluoride 1a and bromobenzene 2a as model substrates to establish catalytic conditions (Table 1). Despite previous successes for nickel-catalyzed decarbonylative C(sp 2 )–C(sp 3 ) reductive cross-coupling, 8 unfortunately, we did not observe the desired coupling product 3a under nickel catalysis. 11 Subsequently, inspired by the remarkable performance of a palladium catalyst and an electron-rich phosphine ligand in decarbonylative coupling reactions, 2 a , c ,12 we found that the decarbonylative reductive coupling product 3a could be detected in 42% yield with minor homo-coupling of 1a in the presence of Pd(OAc) 2 (5.0 mol%) as a catalyst, L1 as a ligand, and Zn dust as a reductant in 2-Me-THF at 130 °C for 24 h. The typical polar solvents such as DMA, DMPA and non-polar solvent toluene had no effect on this transformation (Table 1, entries 2–4).…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Considering certain stability and moderate reactivity of aroyl fluorides among aryl carboxylic acid derivatives, 1 c , d we first selected 4-methoxybenzoyl fluoride 1a and bromobenzene 2a as model substrates to establish catalytic conditions (Table 1). Despite previous successes for nickel-catalyzed decarbonylative C(sp 2 )–C(sp 3 ) reductive cross-coupling, 8 unfortunately, we did not observe the desired coupling product 3a under nickel catalysis. 11 Subsequently, inspired by the remarkable performance of a palladium catalyst and an electron-rich phosphine ligand in decarbonylative coupling reactions, 2 a , c ,12 we found that the decarbonylative reductive coupling product 3a could be detected in 42% yield with minor homo-coupling of 1a in the presence of Pd(OAc) 2 (5.0 mol%) as a catalyst, L1 as a ligand, and Zn dust as a reductant in 2-Me-THF at 130 °C for 24 h. The typical polar solvents such as DMA, DMPA and non-polar solvent toluene had no effect on this transformation (Table 1, entries 2–4).…”
Section: Resultscontrasting
confidence: 95%
“…7 Very recently, a few examples have been reported on decarbonylative C(sp 2 )–C(sp 3 ) reductive cross-coupling of aromatic carboxylic acid derivatives with alkyl electrophiles by Nishihara, Cernak, Weix and Liang. 8 With our continuous interest in reductive cross-coupling of inert aryl electrophiles, 9 herein, we disclose the first decarbonylative C(sp 2 )–C(sp 2 ) reductive cross-coupling of aroyl fluorides with aryl bromides by palladium and cobalt co-catalysis. 10…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above experimental results and literature reports, we proposed the corresponding mechanism cycles for this Ni-catalyzed reductive coupling for the construction C–N bonds (Scheme ). Initially, the active Ni 0 A was formed via reduction of Ni II with Mn followed by the oxidative addition into the N–O bond to form Ni II intermediate B , which then captured the alkyl radical to give Ni III intermediate C .…”
Section: Introductionmentioning
confidence: 90%
“…Nickel, one of the most earth-abundant transition metals, has always been widely used in reductive cross-couplings thanks to its strong catalytic ability, relative low price, and widespread existence . Over the past decade, construction of C–C bonds using this tactic has been deeply explored, and many elegant works have thus been reported . Construction of carbon–hetero bonds using a reductive cross-coupling strategy also received much attention, and many developments have been made in recent years.…”
Section: Introductionmentioning
confidence: 99%